Upper and Lower Weak $(τ_1,τ_2)$-continuity (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the concepts of upper and lower weakly $(τ_1,τ_2)$-continuous multifunctions.Moreover, some characterizations of upper and lower weakly $(τ_1,τ_2)$-continuous multifunctions are investigated.
Keywords: upper weakly $(τ_1,τ_2)$-continuous multifunction; lower weakly $(τ_1,τ_2)$-continuous multifunction